Formulasi Kebijakan Pemerintah Tentang Program Makan Bergizi Gratis di Indonesia - Jati, Andri Kusuma; Azhar, Azhar; Iriani, Atrika (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The Free Nutritious Meal Program is a government policy aimed at improving the nutritional status of school children, reducing stunting, and supporting educational success. This study employs a descriptive qualitative method, with data obtained through digital observation and documentary analysis. Data analysis is conducted using the interactive model of Miles and Huberman, along with the policy process model by William Dunn (2016), which includes problem identification, agenda setting, formulation, adoption, and implementation. The findings indicate that this policy emerged in response to the high stunting rate (21.6% in 2022) and limited access to nutritious food among children from underprivileged families. The government adopted a combined strategy of in-school meal provision and partnerships with local SMEs. Key challenges include infrastructure limitations, budget efficiency, and supervision. Recommended strategies involve decentralized food distribution, collaboration with the private sector, and digital monitoring to ensure the program runs effectively and sustainably.